2011
DOI: 10.1021/om200342f
|View full text |Cite
|
Sign up to set email alerts
|

C–CN Bond Activation of Benzonitrile with [Rh–I(dippe)]

Abstract: The complex [Rh(dippe)(μ-Cl)]2 (1) was reduced with potassium metal to produce the highly reactive Rh–I species [Rh(dippe)(μ-K·THF)]2 (2). 2 was characterized by NMR spectroscopy (31P, 1H) and IR spectroscopy after forming the derivative K[Rh(dippe)(CO)2] (2a). The C–CN bond of benzonitrile was cleaved by oxidative addition when it was reacted stoichiometrically with 2 to form the anionic Rh(I) complex K[Rh(dippe)(CN)(Ph)] (3). 3 has been characterized by NMR spectroscopy (31P, 1H, 13C), and by the use of 13C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Considering that the oxidative additions of phenyl chloride, benzyl chloride, and benzonitrile to a Ni 0 complex have been experimentally reported and theoretically analyzed, we tried to locate a related Ni II hydride phenyl propene complex where the H­(hydride) is cis to the phenyl group but failed to optimize such a structure. This agrees with previous works. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the oxidative additions of phenyl chloride, benzyl chloride, and benzonitrile to a Ni 0 complex have been experimentally reported and theoretically analyzed, we tried to locate a related Ni II hydride phenyl propene complex where the H­(hydride) is cis to the phenyl group but failed to optimize such a structure. This agrees with previous works. , …”
Section: Resultsmentioning
confidence: 99%
“…The concerted oxidative addition of a σ bond to a Ni 0 atom has been analyzed in many experimental and theoretical studies. Thus, we focus here on the ligand-to-ligand H transfer and address the following points. (i) Why is the ligand-to-ligand H transfer preferred over the usual concerted oxidative addition of C–H bond in the case of Ni 0 catalysts?…”
Section: Introductionmentioning
confidence: 99%
“…The 31 P­{ 1 H} SSNMR spectrum (158 K, Figure D) of hydrogenated microcrystalline [1-NBD]­[BAr H 4 ] (2 bar, 1 h, 298 K), features a single very broad resonance centered at δ 89.0, which is assigned to the amorphous zwitterionic decomposition product [1-BAr H 4 ] , which has been independently prepared (Supporting Information). Zwitterionic complexes such as Rh­(PR 3 ) 2 {(η 6 -C 6 H 5 )­BAr H 3 } are well-known. No signals were observed that could be assigned to a σ-alkane complex. For [1-NBD]­[BAr F 4 ] , after hydrogenation for 1 h, two broad closely spaced downfield doublets where observed [δ 105.1, J (RhP) ≈ 180 Hz; δ 102.2, J (RhP) ≈ 190 Hz] that are assigned to σ-alkane complex [1-NBA]­[BAr F 4 ] .…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of these reactions with Co complexes remain elusive. d 10 monomeric [(dippe)Rh] −1 also undergoes the oxidative addition of benzonitrile, 37 while photoirradiation of Cp*Rh(PMe 3 )H 2 (Cp* = η 5 -pentamethylcyclopentadienyl) and Tp'Rh(PMe 3 )H 2 (Tp' = hydrotris(3,5-dimethylpyrazol-1yl)borate) allow that of acetonitrile after kinetically favored C− H activation at the Rh(I) center. 23,38,39 It is unlikely that η 2coordination of the cyano group to the Rh centers occurs, contrasting with the reactions of Ni(0) and Pd(0) because an η 2nitrile complex locates at the energy level higher than that of the C−H activation product and a low-energy pathway from the η 2nitrile complex to either the C−H or C−CN activation is not evident according to DFT calculations.…”
Section: Mechanism Of C−cn Bond Activationmentioning
confidence: 99%